Diagnosing phyllodes tumours of the breast: how successful are our current preoperative assessment modalities?. Issue 10 (23rd August 2018) - Yii, Nathan; Read, Tavis; Tan, Chuan Chien; Ng, Suat Li; Bennett, Ian
Abstract : Background: To assess the efficacy of the diagnostic modalities used in the preoperative assessment of phyllodes tumours. Methods: In this retrospective study of patients treated at Princess Alexandra Hospital, 51 phyllodes tumours in 49 patients diagnosed between 2005 and 2016 were reviewed with regard to their preoperative findings to assess which modalities, including clinical findings, mammography, ultrasound, fine needle aspiration and core biopsy, were most diagnostically discriminating. Data on demographics and management were also collected. Results: While 90.2% of lesions were clinically palpable and an abnormality was seen in 86.1% of lesions subjected to mammography, the findings in relation to these two modalities were essentially those of non‐discriminatory masses. Furthermore, although 100% of the phyllodes lesions were sonographically visible, suspicion of a phyllodes tumour was only noted in 21.6% of cases. Fine needle aspiration yielded results suspicious for phyllodes in 21.1% of cases while core biopsy resulted in confirmed or suspected phyllodes tumour diagnoses in 69.2% of instances. Serial measurements of phyllodes tumours yielded an average growth rate of 8.04 mm per 365 days. Conclusion: In the preoperative diagnosis of phyllodes tumours of the breast, ultrasound was a more discriminating imaging modality compared to mammography, and core biopsy demonstrated a superior accuracy of diagnosis over fine needle biopsy. A significant increase in lesion size over a short timeframe should also alert to the possibility of a phyllodes tumour.